Global Surgery: Effective Involvement of US Academic Surgery. Issue 4 (October 2018) - Mock, Charles; Debas, Haile; Balch, Charles M.; Brennan, Murray; Buyske, Jo; Cusack, James; DeMeester, Steven; Herndon, David; Le Holterman, Ai-Xuan; Jaffe, Bernard; Kandil, Emad; Kauffman, Gordon; et al.
Abstract : N/A: There is an unacceptably high burden of death and disability from conditions that are treatable by surgery, worldwide and especially in low- and middle-income countries (LMICs). The major actions to improve this situation need to be taken by the surgical communities, institutions, and governments of the LMICs. The US surgical community, including the US academic surgical community, has, however, important roles to play in addressing this problem. The American Surgical Association convened a Working Group to address how US academic surgery can most effectively decrease the burden from surgically treatable conditions in LMICs. The Working Group believes that the task will be most successful (1) if the epidemiologic pattern in a given country is taken into account by focusing on those surgically treatable conditions with the highest burdens; (2) if emphasis is placed on those surgical services that are most cost-effective and most feasible to scale up; and (3) if efforts are harmonized with local priorities and with existing global initiatives, such as the World Health Assembly with its 2015 resolution on essential surgery. This consensus statement gives recommendations on how to achieve those goals through the tools of academic surgery: clinical care, training and capacity building, research, and advocacy. Through all of these, the ethical principles of maximally and transparently engaging with and deferring to the interests and needs of local surgeons and their patients are of paramount importance. Notable benefits accrue to US surgeons, trainees, and institutions that engage in global surgical activities.